Mitochondrial genome analysis reveals phylogenetic insights and gene rearrangements in Parupeneus (Syngnathiformes: Mullidae) - Luo, Zhisen; Yi, Murong; Yang, Xiaodong; Wen, Hui; Jiang, Changping; He, Xiongbo; Lin, Hung-Du; Yan, Yunrong (Frontiers in Marine Science, 2024)
Despite the critical role of mitochondrial genomes (mitogenomes) in species identification and evolutionary studies in the genus Parupeneus, current resources are inadequate, given the species richness. Although previous studies have suggested a complex evolutionary history, the detailed mitogenomic variations and their implications remain largely unexplored. Therefore, we sequenced and assembled the mitogenomes of P. barberinoides, P. barberinus, P. biaculeatus, P. crassilabris, P. cyclostomus, P. heptacanthus, P. multifasciatus, and P. chrysopleuron, to enrich the molecular data and provide novel insights into the genetic diversity, evolutionary dynamics and phylogenetics of the family Mullidae. Our analysis revealed a novel gene rearrangement in P. chrysopleuron, Cytb-T-P-CR-Q-I-F-12S-V-16S-ND1-M-ND2, which differed from the conventional sequence of Cytb-T-P-CR-F-12S-V-16S-ND1-I-Q-M-ND2 observed in other species. In the novel rearrangement, four non-coding regions are inserted between ND1 and M, Q and I, I and ψM (tRNA-Met pseudogene), ψM and F. We assume that two tandem duplication/random loss events occur in the CR and IQM, making the entire sequence longer than that in other Parupeneus species. The phylogenetic results indicated that Mullidae formed a sister group relationship with the family Dactylopteridae, contradicting previous studies that identified a sister group relationship between Mullidae and Callionymoidei. The genera Parupeneus and Mullus formed a sister group, and discrepancies were found in the topological structure of the interspecies relationships within the genus Parupeneus compared with those reported by previous studies. Through combined phylogenetic and mitochondrial structural analysis, we found that phylogenetic topology is closely related to mitochondrial structural abnormalities. This study not only expands the mitogenomic dataset available for Mullidae but also underscores the importance of mitochondrial DNA studies in resolving taxonomic ambiguities and understanding the evolutionary history of marine fishes. Our study contributes to the ongoing research on marine fish taxonomy, mitogenomics, and evolutionary biology by providing new insights into the genetic diversity of marine ecosystems.